Incidence of Complication in Neartotal ortotalas Compared to Subtotal Thyroidectomy - alsudani, Ahmed Abbas Hasan; jebur, Adel Hashim (International Journal of Psychosocial Rehabilitation, 2020)
Background: Surgical management of thyroid diseases is still controversial.Complications such as bleeding, hypoparathyroidism and recurrent laryngeal nerve injury (RLNI) represent nearly half of all the complications of thyroid surgery.The latter complication after thyroidectomy, although infrequently encountered, can jeopardize the quality of life. Total thyroidectomy is the choice for the treatment DTC, benign diseases for eradication of disease, it helps in prevention of recurrence, the facilitation of treatment with radioactive iodine and in eliminating the risk of malignant change in radiated thyroid glands. Objective:To assess whether the results support that total thyroidectomy is safe and can be considered as the optimal surgical approach for treating benign thyroid diseases. Patients and Methods:This study was carried out in Baghdad Teaching Hospital during the period from June 2013 to November 2013. It included fifty two (52) patients with different thyroid diseases who underwent different thyroidectomies operations:25 patients who underwent total thyroidectomy(18 patients who underwent primary total thyroidectomy (TT),7 patients who received completion thyroidectomy) (Group 1), 14 patients underwent Near total thyroidectomy (NTT) (Group 2) and 13 patients underwent Subtotal thyroidectomy (STT) (Group 3),so postoperative complication rates regarding hypoparathyroidism and recurrent laryngeal nerve injury(RLNI) were compared. Results:There is no significant differences in the rate of transient or permanent complications (hypoparathyroidism and RLNI) in TT & NTT as compared to STT. Conclusions: Total thyroidectomy can be undertaken safely with a low complication rate. There are no significant difference in the rate of postoperative complications associated with total thyroidectomy compared with subtotal thyroidectomy or total.